Mr Fantastic Meets The Invisible Man: An Illusion of Invisible Finger Stretching. (February 2019) - Byrne, Ailish; Preston, Catherine
Our brain continually integrates bottom-up sensory signals to create a coherent experience of the body. This bodily experience is also constrained by top-down knowledge of body appearance. However, the extent of these constraints has been challenged. Here, we explore top-down limits on body ownership with the invisible finger stretching illusion, in which synchronous visuotactile stimulation applied to the real fingers and an area of empty space elicits the illusion of owning elongating fingers. The results demonstrate that it is possible to experience stretchy fingers like Mr Fantastic without visual stimuli of a fake hand, even if we do not actually feel invisible like The Invisible Man.